When music meets language - Huat, Ang Thiah; Blackburn, Andrew (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Language is a human communication tool and semiotics system, used to convey meaning and express. Similarly, music has its own semiotic set, comparable to that of language, able to evoke specific emotions, sensations without text. Language and music are socially cohesive codes, delineating groups within society and culture, understood by those to whom it „belongs.‟ As language is a social cohesive, defining social groups can be achieved through different musical systems, for example, Malaysian and Western music. As language is dynamic, adjusting to contemporary conditions and technologies, music appears to be undergoing similar adaptation. Audio is compressed for headphone reproduction and MP3 and this reduction in the sonic is changing the aesthetic of what is considered „ideal‟. We shall suggest that there is a similar reductive quality in the content of music that may be compared to the shorthand language of the SMS.